Effect of Celery Extract on Fructose Induced Insulin Resistance Rattus norvegicus - Sukarno, Devitya Angielevi; Mustika, Arifa; Rejeki, Purwo Sri (Folia Medica Indonesiana, 2020)
Diabetes mellitus (DM) is one of the global health problems and in the top 4th ranks as the main cause of death in developing countries (IDF, 2015). The pathogenesis of type II DM involves abnormalities in insulin secretion and activity that leads to insulin resistance. This research aims to study the efficacy of celery (Apiumgraveolens) as a prevention of insulin resistance. In this study, the samples were 45 Wistar rats (Rattus norvegicus), male sex, aged 4-6 weeks, weight 150-175 grams,and had normal fasting blood glucose levels by tested before treatment. The experimental animals were divided into 5 groups, K1 was negative control group (insulin resistance by given 20% fructose 1,86 g/kg BW PO qDay);K2 was positive control group (those given 20% fructose 1,86 g/kg BW PO qDayand standard insulin resistance therapy metformin 500 mg/kg BW PO qDay); the K3 treatment group was given 20% fructose 1,86 g/kg BW PO qDay and celery extract 200 mg/kg BW PO qDay; the K4 treatment group was given fructose 20% 1,86 mg/kg BW PO qDay and celery extract 400 mg/kg BW PO qDay; and the K5 treatment group was given fructose 20% 1,86 mg/kg BW PO qDay and celery extract 600 mg/kg BW PO qDay. The treatment had been given every day for 60 days.Fasting blood glucose levels were measured using a Glucometer. Fasting blood insulin levels were measured using ELISA, HOMA-IR was calculated using a standardized formula, and GLUT4 protein expression was measured using immunohistochemistry. It the end of the intervention, there was a significant decreased in fasting blood glucose (FBG) in K4 group compared with K1 (p <0.05), insulin resistance in K1 was characterized by a higher HOMA-IR value compared to the therapy group, especially K4 and K5 (p <0.05). There was an increase in GLUT-4 expression on K4 and K5 compared with K1 (p <0.05). It can be concluded that celery extract has antihyperglycemia effect and furthermore it can prevent insulin resistance condition.